Indoleamine-2,3-dioxygenase activity in experimental human endotoxemia - Padberg, Jan-Sören (BioMed Central, 2012)
BACKGROUND: Excessive tryptophan metabolism to kynurenine by the rate-limiting enzyme endothelial indoleamine 2,3-dioxygenase 1 (IDO) controls arterial vessel relaxation and causes hypotension in murine endotoxemia. However, its relevance in human endotoxemia has not been investigated so far. We thus aimed to study changes in blood pressure in parallel with tryptophan and kynurenine levels during experimental endotoxemia in humans. FINDINGS: Six healthy male volunteers were given E. coli lipopolysaccharide (LPS; 4 ng/kg) as a 1-min intravenous infusion. They had levels of soluble E-Selectin and soluble vascular cell adhesion molecule-1 as well as IDO activity assessed as the kynurenine-to-tryptophan plasma ratio by liquid chromatography-tandem mass spectrometry at various time points during a 24 h time course. During endotoxemia, IDO activity significantly increased, reaching peak levels at 8 h after LPS infusion (44.0 ± 15.2 vs. 29.4 ± 6.8 at baseline, P<0.0001). IDO activity correlated inversely with the development of hypotension as shown by random effects linear regression models. Finally, IDO activity exhibited a kinetic profile similar to that of soluble endothelial-specific adhesion molecules. CONCLUSIONS: LPS is a triggering factor for the induction of IDO in men. Our findings strongly support the concept that the induction of IDO in the vascular endothelium contributes to hypotension in human sepsis.